Low molecular weight thiols: glutathione (GSH), mycothiol (MSH) potenail antioxidant compound from actinobacteria - Anita Garg, Bhavana soni, Balwant Singh Paliya, Smarti Verma, Vishwjeet Jadaun (Journal of Applied Pharmaceutical Science, 2013)
The class of Actinobacteria is a large group of gram-positive bacteria and having high G+C content. Actinobacteria also produced curious compound like thiols mainly Mycothiol (MSH) and Glutathione (GSH). MSH is also known as mycothiol and comprised of a cysteine residue with an acetylated amino group which is linked to glucosamine to inositol but Glutathione (GSH) having gamma peptide linkage between cysteine group which is attached by normal peptide linkage to a glycine and the carboxyl group of the glutamate side-chain. These thiols play a key role in maintaining a reducing environment in the cell, which is necessary for regular metabolic activities and represent adaptation under stress condition for survival of organisms. Both Mycothiol and glutathione (GSH) having property to protect cells against oxygen toxicity but MSH shows 7 fold slower ability to resistance of autoxidation compare to GSH but GSH is absent in archaebacterium and rarely found in Streptomycetes strains (Streptomyces lactamdurans). In this review article we discussed about the GSH and MSH structure, properties and how GSH is better than MSH in the case of antioxidant production.
Keywords: Glutathione (GSH), Mycothiols (MSH), Actinobacteria,